Pengaruh penanaman modal dalam negeri, penanaman modal asing, pengeluaran pemerintah dan tenaga kerja terhadap pertumbuhan ekonomi di provinsi pulau Jawa dalam perspektif ekonomi Islam - Rahmadhani, Mutia; Malik, Anas; Rahman, Taufiqur (STAI Auliaurrasyidin Tembilahan, 2025)
Economic growth in Islamic economic teachings is strengthened in the Quran, as-sunnah, and the writings of previous scholars. The growth and development of Islamic economics are reflected in the development of human resources and nature to strengthen human dignity, not only including financial fulfillment, but also desires and preparation for life in the afterlife. This study aims to determine the effect of Domestic Investment, Foreign Investment, Government Spending and Labor on Economic Growth in the Province of Java Island in the Perspective of Islamic Economics. The study used panel data from 6 provinces in Java Island. The results of the study showed that the selected model was the fixed effect model test which stated the results of the t-test that the PMDN variable had a positive and significant effect on economic growth, the PMA variable had a positive but insignificant effect on economic growth, the government spending variable had a positive and significant effect on economic growth and the labor variable had a negative and insignificant effect on economic growth.